Aneuploidy during the onset of mouse embryo development - Pauerova, Tereza; Radonova, Lenka; Kovacovicova, Kristina; Novakova, Lucia; Skultety, Michal; Anger, Martin (Reproduction, 2020)
Aneuploidy is the most frequent single cause leading into the termination of early development in human and animal reproduction. Although the mouse is frequently used as a model organism for studying the aneuploidy, we have only incomplete information about the frequency of numerical chromosomal aberrations throughout development, usually limited to a particular stage or assumed from the occurrence of micronuclei. In our study, we systematically scored aneuploidy in in vivo mouse embryos, from zygotes up to 16-cell stage, using kinetochore counting assay. We show here that the frequency of aneuploidy per blastomere remains relatively similar from zygotes until 8-cell embryos and then increases in 16-cell embryos. Due to the accumulation of blastomeres, aneuploidy per embryo increases gradually during this developmental period. Our data also revealed that the aneuploidy from zygotes and 2-cell embryos does not propagate further into later developmental stages, suggesting that embryos suffering from aneuploidy are eliminated at this stage. Experiments with reconstituted live embryos revealed, that hyperploid blastomeres survive early development, although they exhibit slower cell cycle progression and suffer frequently from DNA fragmentation and cell cycle arrest.
Keywords: blastomery; Animals; Female; Embryo, Mammalian; aneuploidie; fertilizace in vitro; ženské pohlaví; Cell Cycle; Zygote; zygota; Mice; těhotenství; Blastomeres; myši; buněčný cyklus; Embryonic Development; zvířata; embryonální vývoj; Aneuploidy; Pregnancy; embryo savčí; Fertilization in Vitro